2017
DOI: 10.1002/asia.201701657
|View full text |Cite
|
Sign up to set email alerts
|

A Library of Multipurpose Supramolecular Supergelators: Fabrication of Structured Silica, Porous Plastics, and Fluorescent Gels

Abstract: Supramolecular gels find applications in various fields. Usually, a specific gelator is useful only for a specific application. This one-gelator-one-application format is one factor that limits the usefulness of supramolecular gels. We report the synthesis of a library of gelators from a common core by using a click-chemistry approach. Thus, the click reaction of β-azido-4,6-O-benzylidene-galactopyranoside (1) with various alkynes gave 11 different gelators having varying gelation abilities. Whereas gelators h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 103 publications
0
11
0
Order By: Relevance
“…Krishnan et al reported the synthesis and gelation properties of a series of 11 4,6benzylidene acetal protected β-triazole derivatives from D-galactose ( Figure 33) [80]. These compounds were tested in hydrocarbon solvents and oils with CGCs in the range of 0.10 to 3.58 wt %.…”
Section: C-1 Triazole Glycoside Derivativesmentioning
confidence: 99%
See 3 more Smart Citations
“…Krishnan et al reported the synthesis and gelation properties of a series of 11 4,6benzylidene acetal protected β-triazole derivatives from D-galactose ( Figure 33) [80]. These compounds were tested in hydrocarbon solvents and oils with CGCs in the range of 0.10 to 3.58 wt %.…”
Section: C-1 Triazole Glycoside Derivativesmentioning
confidence: 99%
“…The aromatic derivatives formed gels in organic solvents, but not in oil. An anthracene-containing gelator 48f showed interesting fluorescent properties and could have applications in various fields [80]. Figure 33) [80].…”
Section: C-1 Triazole Glycoside Derivativesmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these, the formation of a well-defined architecture of nano or meso structured silica by sol-gel transcription of a supramolecular gel has been extensively studied [5,27,124]. A library of eleven organogelators ( 40 , Figure 29) has been designed and synthesized utilizing azido 4,6- O -benzylidene-β- d -galactopyranose as a common building block utilizing click chemistry [125]. Gelators with an alkyl chain on the triazole moiety, gelated alkanes, and tetraethyl orthosilicate (TEOS), those having an aromatic substituent on the triazole moiety, caused congelation of aromatic solvents.…”
Section: Applicationsmentioning
confidence: 99%